Masayuki TANIMOTO and R. Bin WONG, editors: Public Goods Provision in the Early Modern Economy: Comparative Perspectives from Japan, China, and Europe - Jiarui Wu (Asian Studies, 2023)
Previous studies regarding the emergence and development of social systems have often been based on the study of European nations, which largely ignores the fact that other nations also underwent the process in patterns that are either similar or strikingly different from the European one. Contemporary researchers have identified this flaw and thus sought to address it by studying the emergence and development of social systems in non-European nations rather than assuming that the European model is the standard. It is in line with this new school of thought that Bin Wong and Masayuki Tanimoto explore social development in Japan and compare it with Europe. In their book Public Goods Provision in the Early Modern Economy: Comparative Perspectives from Japan, China, and Europe, the authors provide readers with a general overview of the systems for public goods provision in early modern Japan, while also offering comparison examples from Europe, primarily from Prussia.